Compressor equipment for enhancing efficiency of solid organic waste processing plants - A. V. Burakov; A. A. Kotlov; A. A. Levikhin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article describes the experience of the Compressor holding company in the creation of compressor equipment for various industries. The use of compressors as part of complexes for the processing of organic waste in the framework of solving urgent environmental problems has been demonstrated. The process of compression of synthesis gas to increase the efficiency of the processing process has been investigated. To ensure stable parameters, reliable operation of syngas reciprocating compressors is required in wide ranges of operating parameters. Ensuring the operability of the compressor in wide ranges of parameter variation requires multivariate calculations in order to find the best design parameters of the compressor. A compressor is proposed for the most efficient implementation of the task and its characteristics are calculated.